2008
DOI: 10.1186/1471-2164-9-312
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput gene and SNP discovery in Eucalyptus grandis, an uncharacterized genome

Abstract: Background: Benefits from high-throughput sequencing using 454 pyrosequencing technology may be most apparent for species with high societal or economic value but few genomic resources. Rapid means of gene sequence and SNP discovery using this novel sequencing technology provide a set of baseline tools for genome-level research. However, it is questionable how effective the sequencing of large numbers of short reads for species with essentially no prior gene sequence information will support contig assemblies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
412
5
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 431 publications
(472 citation statements)
references
References 39 publications
(46 reference statements)
46
412
5
9
Order By: Relevance
“…Eucalypts are preferentially outcrossing with late-acting post-zygotic selfincompatibility resulting in outcrossing rates that can exceed 90% 1 , high levels of nucleotide variation 23,24 and accumulation of genetic load and expression of inbreeding depression 4 . A microsatellite survey of BRASUZ1 and its inbred siblings indicated putative hotspots of genetic load (Supplementary Information section 4).…”
Section: Genetic Load and Heterozygositymentioning
confidence: 99%
“…Eucalypts are preferentially outcrossing with late-acting post-zygotic selfincompatibility resulting in outcrossing rates that can exceed 90% 1 , high levels of nucleotide variation 23,24 and accumulation of genetic load and expression of inbreeding depression 4 . A microsatellite survey of BRASUZ1 and its inbred siblings indicated putative hotspots of genetic load (Supplementary Information section 4).…”
Section: Genetic Load and Heterozygositymentioning
confidence: 99%
“…The resulting ESTs are aligned the gene-enriched sequences to identify SNPs (Barbazuk et al 2007). This approach can be successful even in cases for which reference genomic sequences are not available (Novaes et al 2008;Buggs et al 2009). Once identified, SNPs are converted into genetic markers and are used to genotype the mapping population and build a genetic map.…”
Section: Conversion Of Putative Snps To Genetic Markersmentioning
confidence: 99%
“…Like DArT, they are largely bi-allelic, but, similarly, their high abundance should ameliorate this limitation. Published accounts of the SNP resource are still rare for eucalypts, but sequencing of the transcriptome and resequencing genome fractions or genes using conventional or next-generation sequencing has confirmed that large numbers of SNPs will be available (Külheim et al 2009;Novaes et al 2008;Poke et al 2003). Assay methods have been used that accommodate the complexity of SNP genotyping in the highly heterozygous eucalypt genome (Sexton et al 2010b), although at a relatively low throughput of less than 100 multiplexed SNPs.…”
Section: Molecular Marker Resourcesmentioning
confidence: 99%